CULTURAL ASPECTS OF LIFE AND SPECIFIC QUALITIES OF THE CRAFTS OF THE EMIRATE OF BUKHARA AND RUSSIAN-EUROPEAN INFLUENCE ON THE EMIRATE (IN XIX-XX CENTURIES) - Mubinov Muhammadali (Western European Studies, 2024)
this article discusses the features of the handicraft culture of the Bukhara Emirate, which has been formed over the centuries. Along with fragments of works by figures of different spheres of the selected region, one can also get acquainted with the prospects for the gradual penetration of the Russification policy into various activities of the region.
Keywords: craft; art; culture; ornamentation